Peatland Forest Fire: Mitigation and Conservation Management in Brunei Darusssalam - Wida Susanty Haji Suhaili (Jurnal Silvikultur Tropika, 2022)
Peat fire is the main cause of haze, and within ASEAN region, this is known as transboundary haze. Transboundary haze issue has been lingering in this region especially with the climate change. Hence, it is important to stop fire from happening. It is the top priority of the research because early detection and suppression of fire are the only way to minimize damages and losses. This paper covers the research taken from 2016 up to date in the mitigation and conversation management in Brunei Darussalam. The approach used an action research approach where the adoption of technology in particular wireless sensor in the form of Internet of Things was used, and the approaches were taken by the respective stakeholders within the context to minimize peatland forest fire. The forest biodiversity management as well as the whole nation approach to address the climate change will also be shared towards the country’s target aiming to preserve 55% of its forest as permanent forest reserve for the future. Keywords: Mitigations, Conservation, Management Peatland Forest Fire